The Phenomenon of High Paylater and Financial Literacy in The Consumptive Behavior of Generation Z In Medan City - Purwita; Alexander Parhusip, Austin; Ramadhan, M. Rafly; Dwi Ananda, Rendy (EKONOMIKA SYARIAH : Journal of Economic Studies, 2025)
Technological advances have brought convenience to various aspects of life, especially payment systems and financial service products. The impact of developments in technological advances in financial services and payment systems is of great interest and attracts the attention of the public, especially Generation Z who are aware of digital developments in the current era, so curiosity about trying online shopping using the Paylater feature is increasing. The aim of this research is to review the factors inhibiting consumptive behavior and supporting the high level of Paylater, after that to determine financial literacy skills in managing lifestyle and consumptive behavior, to find out the solutions applied by Generation Z in minimizing Paylater users and consumptive behavior in generation Z in Medan City, North Sumatra. Triangulation data analysis techniques are assisted by the N-Vivo 12 Plus Tools. The supporting factors for PayLater's high level of consumer behavior in generation Z are ease of use, ease of access, lifestyle, lots of discounts and promos, financial literacy skills in managing the lifestyle of generation Z, namely financial management planning, recording income and expenses, not following trends and hedonism, solutions applied by Generation Z in minimizing PayLater users and consumptive behavior, namely not being tempted by promos and discounts, being able to differentiate between needs and desires, self-control over the influence of social media. Kemajuan teknologi telah membawa kemudahan dalam berbagai aspek kehidupan terutama sistem pembayaran dan produk layanan keuangan. Dampak perkembangan kemajuan teknologi layanan keuangan dan sistem pembayaran sangat di minati dan menarik perhatian masyarakat terutama kalangan generasi Z yang melek akan perkembangan digital di era saat ini sehingga rasa ingin tahu untuk mencoba berbelanja online dengan menggunakan fitur Paylater semakin meningkat. Tujuan penelitian ini untuk meninjau untuk faktor-faktor penghambat perilaku konsumtif dan pendukung tingginya Paylater, setelah itu untuk mengetahui kemampuan literasi keuangan dalam mengatur gaya hidup dan perilaku konsumtif, untuk mengetahui solusi yang diterapkan generasi Z dalam meminimalisir pengguna Paylater dan perilaku konsumtif pada generasi Z di Kota Medan Sumatera Utara. Teknik analisis data Triangulasi dibantu oleh Tools N-Vivo 12 Plus. Factor pendukung tingginya PayLater dalam perilaku konsumtif generasi Z yaitu kemudahan pengguna, kemudahan akses, gaya hidup, banyaknya diskon dan promo, kemampuan literasi keuangan dalam mengatur gaya hidup generasi Z yaitu adanya perencanaan pengelolaan keuangan, pencatatan pemasukan dan pengeluaran, tidak mengikuti trend dan hedonism, solusi yang diterapkan generasi Z dalam meminimalisir pengguna PayLater dan perilaku konsumtif yaitu tidak tergiur dengan promo dan diskon, mampu membedakan kebutuhan dan keinginan, pengendalian diri terhadap pengaruh media social.